Association Between Dietary Patterns and All-Cause Mortality in Individuals with Hypertension and Osteoporosis: A Retrospective Cohort Study - Guan J; Ding L; Wang Y; Zhu Z; Pan M; Du L; Yin N (Journal of Multidisciplinary Healthcare)
Jianhua Guan,* Liang Ding,* Yifei Wang,* Zhongsheng Zhu,* Mingmang Pan, Li Du, Nuo Yin Department of Orthopedics, Shanghai Jiao Tong University Affiliated Sixth People’s Hospital South Campus (Shanghai Fengxian District Central Hospital), Shanghai, 201599, People’s Republic of China*These authors contributed equally to this workCorrespondence: Nuo Yin, Department of Orthopedics, South Hospital of the Sixth People’s Hospital Affiliated to Shanghai University of Medicine & Health Sciences (Shanghai Fengxian District Central Hospital), No. 6600 South Fenggong Road Fengxian District, Shanghai, 201599, People’s Republic of China, Tel +86 18916174997, Email nuoyindoc_SUMHS@outlook.comObjective: To explore the association of dietary patterns with all-cause mortality in individuals with hypertension and osteoporosis.Methods: Data on individuals aged ≥ 20 years who completed bone mineral density tests were retrieved from the National Health and Nutrition Examination Survey database. Three dietary patterns were Mediterranean Diet Score (MeDS), Alternative Health Eating Index (AHEI) and Dietary Approaches to Stop Hypertension (DASH). The relationships between osteoporosis (OS), hypertension (HTN) and all-cause mortality were assessed by multivariate and univariate Cox proportional hazard models, with hazard ratios (HRs) and confidence intervals (CIs). Interaction of OS and HTN on overall mortality was evaluated by the attributable proportion (AP), relative excess risk due to interaction (RERI), and synergy index (S). Associations of three dietary patterns with all-cause mortality were explored in different groups, including adults with HTN or OS only, and adults with or without OS and HTN. Subgroups of gender and menopausal state were further evaluated these associations.Results: Of the total 16,358 participants, 1383 (5.84%) died during the follow-up duration. Participants who had HTN (HR=1.272, 95% CI: 1.083– 1.494) or OS (HR=1.674, 95% CI: 1.262– 2.221) had a higher risk of overall mortality. There was an interaction between HTN and OS on overall mortality (RERI=0.677, 95% CI: 0.070– 1.285; AP=0.293, 95% CI: 0.094– 0.492; SI=2.070, 95% CI: 1.124– 3.813). The AHEI-2010, MeDS, and DASH were related to overall mortality in individuals with OS and HTN. The MeDS and DASH were concerned with all-cause mortality in HTN patients without OS. The MeDS and AHEI-2010 were linked to overall mortality in adults without OS and HTN.Conclusion: The impacts of different dietary patterns were differences in multi-feature population. It was suggested that reasonable dietary management is beneficial to the prognosis of different populations.Keywords: hypertension, osteoporosis, all-cause mortality, Mediterranean diet score, alternative health eating index (AHEI-2010), dietary approaches to stop hypertension